Do Japanese Acquisitions Improve Target Firm Financial Performance? A Case Study in Thailand - Sakunasingha, Benjalux; Ishido, Hikari; Liang, Licheng (Journal of Multidisciplinary in Social Sciences, 2025)
This paper examines how mergers and acquisitions (M&A) by Japanese firms affect the performance of local companies in Thailand. Japan is one of Thailand’s three largest acquirer countries, along with the United States and China, making this case an important one to study. The empirical analysis uses a paired t-test based on company-level financial data. The results show that M&A activity by Japanese firms leads to changes in the average values of several financial ratios and indicators, including Return on Equity. In contrast, changes in Return on Assets and Gross Profit are not statistically significant. Although further research is needed to establish causality, the observed performance shifts may be linked to cross-border transfers of intangible assets and synergy benefits gained through the M&A process. Overall, the statistical findings suggest qualitative changes in the financial items and ratios examined, following cross-border acquisitions by Japanese firms.